Electrochemically wired cathode titanates for Li-ion batteries - Küzma, Mirjana; Jamnik, Janko; Gaberšček, Miran (Anali PAZU, 2022)
Cathode materials Li2MTiO4, where M = Fe, Mn and Ni, were synthesized via modified citrate sol-gel procedure. Three members of the titanate cathode family crystallize in the cation disorder cubic rock-salt structure with a space group Fm3m. We demonstrate, for the first time, a considerable electrochemical activity of all three members of lithium transition-element titanates: Li2FeTiO4, Li2MnTiO4 and Li2NiTiO4. We also show their rate performance, cyclability and electronic conductivity in air and argon atmosphere. An effort has been made to understand the lithium exchange mechanism on electrochemical cycling of all three analogues and for this purpose structural in-situ techniques such as X-ray powder diffraction, Mössbauer, XAS and PES spectroscopies were used.
Keywords: Li-ion battery; cathode material; lithium iron titanate; lithium manganese titanate; lithium nickel titanate; in-situ structural methods